RISK FACTORS OF OBESITY IN ADOLESCENCE: A CASE CONTROL STUDY - Novianti, Siti; Lina, Nur; Gustaman, Rian Arie; Hanifah, Alisa Siti (International Journal of Health Science & Medical Research, 2025)
Obesity in adolescents needs attention because it can persist into adulthood and increase the risk of degenerative diseases. In Tasikmalaya district, there has not been much research related to obesity risk factors, including with case control study. This research aims to analyze the risk factors associated with obesity in adolescents. The research sample consists of teenagers from a private school in Tasikmalaya Regency. This study uses a case-control design, with a total of 32 cases (total sampling) and 64 controls, resulting in a total sample of 96 students. The independent variables are junk food consumption, soft drink consumption, vegetable and fruit consumption, physical activity, screen time, and sleep duration. Data collection techniques were conducted through interviews and food recalls, as well as measuring obesity using the BMI indicator. Data analysis employed the chi-square test at a 95% confidence level. The research results indicate that the variables of junk food consumption (p-value=0.025; OR=3.1), soft drink consumption (p-value=0.017; OR=3.3), vegetable consumption (p-value=0.012; OR=3.4), fruit consumption (p-value=0.017; OR=3.2), physical activity (p-value=0.002; OR=4.5), screen time (p-value=0.017; OR=3.2), and sleep duration (p-value=0.035; OR=2.8) have a significant relationship with the incidence of obesity in adolescents. Thus, the factors of food consumption, physical activity, screen time, and sleep duration are variables that increase the risk of obesity in adolescents.